Multiattribute Response of Maize Genotypes Tested in Different Coastal Regions of Brazil - Lúcio Borges de Araújo; Mario Varela Nualles; Mirian Fernandes Carvalho Araújo; Carlos Tadeu dos Santos Dias (International Journal of Agronomy)
This work applies the three mode principal components analysis to analyze simultaneously the multiple attributes; to fit of models with additive main effects and multiplicative interaction effects (AMMI models) and the regressions models on sites (SREG models); to evaluate, respectively, the multivariate response of the genotype × environment interaction and the mean response of 36 genotypes of corn tested in 4 locations in Brazil. The results were presented by joint plots to identify the best genotypes for their adaptability and performance in the set of attributes.